2019
DOI: 10.1111/ene.14129
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as potential biomarkers for genetic generalized epilepsies: a three microRNA panel

Abstract: Background and purpose Genetic generalized epilepsies (GGEs) encompass a group of syndromes of mainly genetic causes, characterized by the involvement of both hemispheres. MicroRNAs (miRNAs) are small non‐coding RNAs with a critical role in the regulation of neuronal biological processes through gene expression modulation. Dysregulated miRNA expression has been shown in epilepsy. Due to their stability in biological fluids like serum, miRNAs have assumed a prominent role in biomarker research. Our aim was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
(43 reference statements)
0
10
0
1
Order By: Relevance
“…On the other hand, for genetic generalized epilepsies, it may be more connection with microRNAs. Martins-Ferreira et al found that miR-146a, miR-155, and miR-132 may partake in genetic generalized epilepsies(GGE) epileptogenesis and they reported that the three circulating microRNAs have potential value to be GGE biomarker (37). In particular, the striking up-regulation of miR-132 in epilepsy has been described in several experimental articles (38)(39)(40).…”
Section: Micrornas As Potential Diagnostic Biomarkers For Epilepsymentioning
confidence: 98%
“…On the other hand, for genetic generalized epilepsies, it may be more connection with microRNAs. Martins-Ferreira et al found that miR-146a, miR-155, and miR-132 may partake in genetic generalized epilepsies(GGE) epileptogenesis and they reported that the three circulating microRNAs have potential value to be GGE biomarker (37). In particular, the striking up-regulation of miR-132 in epilepsy has been described in several experimental articles (38)(39)(40).…”
Section: Micrornas As Potential Diagnostic Biomarkers For Epilepsymentioning
confidence: 98%
“…Serum of miR-146a and miR-155 levels are also significantly upregulated in genetic generalized epilepsy patients. Martins-Ferreira et al (2020) suggested that the combined serum levels of miR-132, miR-146a, and miR-155 could discriminate between genetic generalized epilepsy patients and controls with high specificity and sensitivity.…”
Section: Mirnas As Biomarkers Of Epilepsymentioning
confidence: 99%
“…Currently, with the emerging research of epigenetic biomarkers, MicroRNAs (miRNAs) have been assumed to play a significant role. MiRNA molecules 19-25 nucleotides long regulate gene expression as post-transcriptional modifiers [ 11 ]. Differential expression of more than 100 miRNAs has been reported in epilepsy.…”
Section: Role Of Genes Genetics and Inheritancementioning
confidence: 99%
“…Differential expression of more than 100 miRNAs has been reported in epilepsy. Among them, because of their predominant role in biological processes related to epilepsy, such as neurodegeneration, neuronal growth, and neuroinflammation, miR-132, miR-155, and miR-146a have been highlighted primarily [ 11 ]. Some cases of genetic mutations result in the core symptom of epilepsy, while changes in a few of the genes are responsible for malformations in the gross development of the brain that cause seizures.…”
Section: Role Of Genes Genetics and Inheritancementioning
confidence: 99%